Systematic review and appraisal of clinical practice guidelines on pelvic organ prolapse using the AGREE II tool. Issue 6 (8th June 2021) - Tsiapakidou, Sofia; Nygaard, Christiana Campani; Falconi, Gabriele; Pape, Janna; Betschart, Cornelia; Doumouchtsis, Stergios K; ,
Abstract: Aims: To systematically evaluate the content and quality of national and international clinical guidelines on pelvic organ prolapse (POP). Methods: We searched medical databases and organizations websites, to identify national and international guidelines on diagnosis and management of POP. Five authors independently assessed guidelines using the validated AGREE II tool. Its six domains include (1) scope and purpose, (2) stakeholder involvement, (3) rigor of development, (4) clarity of presentation, (5) applicability, and (6) editorial independence. Results: Eight guidelines met the inclusion criteria. Three hundred and thirteen different recommendations were identified. One hundred and ninety‐nine recommendations were comparable across guidelines. Thirty‐one recommendations were not supported by research evidence. Assessment by history and physical examination using the POP quantification system and consideration of imaging were recommendations featuring in all guidelines. Conservative treatment recommendations namely pelvic floor muscle training and vaginal pessaries were also found in all guidelines. Regarding surgical management, patient counseling, treating only symptomatic POP, consideration of apical fixation during surgical treatment, and use of biological or synthetic implants in recurrent cases were recommendations in all guidelines. Overall, the highest median scores were in the domains "scope and purpose" and "rigor of development". The lowest median score was for applicability (28.3%). Although the median score of "editorial independence" was high (85.4%), variability was also substantial (interquartile range: 12.5–100). Conclusion: We identified variations in quality and deficiencies in certain areas, especially "applicability" and "editorial independence." Improvements in these key domains may enhance the quality and clinical impact of clinical practice guidelines.